Analysis of Leadership Commitment and the Role of Internal Auditors Towards the Implementation of the Internal Control System and Its Impact on the Quality of Financial Reports of the Ministry/Government Agency of the Republic of Indonesia - Cynthya Artha Kirana, RR; Hidayah, Nurul (International Journal of Social Science, Education, Communication and Economics, 2024)
The increasing number of corruption cases involving Ministries and/or State Institutions indicates weaknesses in the internal control system in state financial management in Ministries and/or State Institutions. Internal Control System as an integral process in actions and activities carried out continuously by management and all employees. This study aims to analyze the analysis of leadership commitment and the role of internal auditors in the implementation of internal control systems and their impact on the quality of financial reports of ministries/government institutions of the Republic of Indonesia. The method used is quantitative research, with the research population of examiners working at the State Financial Auditorate III at the BPK RI. With the sample criteria of employees with the position of Junior Expert Examiner already have a minimum of 10 years of experience in conducting audits, have led an audit team, and are responsible for the results of the audit team. The number of employees with these criteria is 80 employees. The results of the study showed that Leadership Commitment has a significant positive effect on the Implementation of Internal Control Systems with a p-value of 0.000 <0.05 (H1 Accepted). The Role of Internal Auditors has a significant positive effect on the Implementation of Internal Control Systems with a p-value of 0.000 <0.05 (H2 Accepted). Leadership Commitment does not have a significant effect on the Quality of Financial Reports with a p-value of 0.535>0.05 (H3 Rejected). The Role of Internal Auditors does not have a significant effect on the Quality of Financial Reports with a p-value of 0.181>0.05 (H4 Accepted). The Implementation of Internal Control Systems has a significant positive effect on the Quality of Financial Reports with a p-value of 0.000 <0.05 (H5 Accepted).